An analysis of the library usage patterns of law students of the U.P. College of Law - Balidoy, Rosemarie D. (2006)
This research sought to determine the library usage patterns of students the University of the Philippines College of Law in relation to their personal attributes, legal research needs, and the library's facilities, resources and services.